Habitat value of constructed breeding pools for the endangered Sonoma population of California tiger salamander. Issue 3 (6th February 2023) - Cook, David G.; Stemle, Leyna R.; Stokes, David L.; Messerman, Arianne F.; Meisler, Julian A.; Searcy, Christopher A.
Abstract: Habitat creation is a common element of efforts to recover populations threatened by altered habitat. Unfortunately, human‐created habitats do not necessarily support re‐establishment of target species. We investigated the value of constructed vernal pools as breeding habitat for the endangered Sonoma County population of California tiger salamanders ( Ambystoma californiense ) by conducting 19 years of larval surveys in 118 pools that were natural ( n = 40), constructed ( n = 70), or natural with substantial human alterations (human‐altered, n = 8). California tiger salamander larval densities in human‐altered and natural pools declined over the study period, while larval densities in constructed pools showed non‐negative trends. Larval declines in natural pools may be attributed to long‐term degradation of the surrounding terrestrial habitat. Mean larval densities over the course of the study were equivalent between constructed and natural pools, when corrected for pool morphometry. In contrast, human‐altered pools had lower larval densities. To assure consistent California tiger salamander breeding, pools needed to be ≥30 cm deep and 240 m 2 in area, with deeper (50–70 cm) and larger (1, 600–1, 800 m 2 ) pools providing increased larval productivity. Over the study, there was no evidence of decrease in the rate of colonization of new pools. We conclude that constructed pools can be important tools in the recovery of imperiled pool‐breeding amphibians if proper design elements for the target species are considered. Abstract : Our results, based on surveys of 118 pools over 19 years, show that appropriately designed constructed pools can support similar densities of amphibian larvae as natural vernal pools. Pool construction can serve as an effective restoration tool in areas where natural pools have been removed, degraded, or altered, or are isolated. Thus, constructed pools can provide valuable breeding habitat for imperiled pond‐breeding amphibians like the endangered Sonoma population of California tiger salamander.